2009
DOI: 10.1523/jneurosci.0198-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

An Acquired Channelopathy Involving Thalamic T-Type Ca2+Channels after Status Epilepticus

Abstract: Some epilepsies are linked to inherited traits, but many appear to arise through acquired alterations in neuronal excitability. Status epilepticus (SE) is associated with numerous changes that promote spontaneous recurrent seizures (SRS), and studies have suggested that hippocampal T-type Ca 2ϩ channels underlie increased bursts of activity integral to the generation of these seizures. The thalamus also contributes to epileptogenesis, but no studies have directly assessed channel alterations in the thalamus du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 77 publications
(115 reference statements)
0
36
0
Order By: Relevance
“…25 These synaptic alterations may not only result from cell loss but also from abnormal structural plasticity at the level of single cells. Indeed, a recent study in pilocarpine-induced status epilepticus showed marked long-term increases in T-type calcium channels in the midline region, 26 further supporting a role for altered distribution of receptor channels in thalamic hyperexcitability. Thalamic abnormalities in our patients extended to posterior divisions corresponding to the location of the medial pulvinar.…”
Section: Mri Acquisitionmentioning
confidence: 82%
“…25 These synaptic alterations may not only result from cell loss but also from abnormal structural plasticity at the level of single cells. Indeed, a recent study in pilocarpine-induced status epilepticus showed marked long-term increases in T-type calcium channels in the midline region, 26 further supporting a role for altered distribution of receptor channels in thalamic hyperexcitability. Thalamic abnormalities in our patients extended to posterior divisions corresponding to the location of the medial pulvinar.…”
Section: Mri Acquisitionmentioning
confidence: 82%
“…The latter has been demonstrated to relate to the modulation of Ca V 3.2 transcription by REST (16,18). Interestingly, highly dynamic changes of Ca V 3.2 expression have been observed in epileptogenesis after brain insults in thalamic as well as hippocampal principal neurons (14,15). In hippocampal CA1 pyramidal cells, Ca V 3.2 mRNA is transiently up-regulated early in epileptogenesis that is triggered by an episode of status epilepticus (SE), leading to an increase in the propensity for intrinsic burst-firing (15,45).…”
Section: Discussionmentioning
confidence: 99%
“…Gain-of-function mutations in the Ca V 3.2 gene are associated with idiopathic generalized/absence epilepsy (11)(12)(13). Likewise, acquired increases in thalamic and hippocampal Ca V 3.2 expression contribute to the development of chronic epilepsy (14,15). In addition, overexpression of Ca V 3.2 channels in myocytes may result in the development of several cardiac dysfunctions, including ventricular arrhythmias (16,17).…”
Section: Low Voltage-activated (T-type) Camentioning
confidence: 99%
“…These mice are deficient in one copy of the gene that encodes the presynaptic protein SNAP-25, which interacts with HVA channels. Finally, in the pilocarpine and electrical kindling models of limbic epilepsy, augmented T-type currents are ob-served in CA1 hippocampal neurons, along with increased burst-firing and neuronal death, findings that are attenuated in Ca V 3.2 knockout mice (Faas et al 1996;Hendriksen et al 1997;Su et al 2002;Becker et al 2008;Graef et al 2009). …”
Section: Ca V 3 (T-type) Channel and Epilepsy Animal Models Of T-typementioning
confidence: 99%